2020
DOI: 10.1038/s41598-020-64485-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of tRNA fragments by electrochemical direct detection in small volume biofluid samples

Abstract: Elevated levels of transfer RNA (tRNA) fragments were recently identified in plasma samples from people with epilepsy in advance of a seizure, indicting a potential novel class of circulating biomarker. Current methods for detection and quantitation of tRNA fragments (tRFs) include northern blotting, RNA sequencing or custom Taqman-based PCR assays. The development of a simple, at home or clinic-based test, would benefit from a simple and reliable method to detect the tRFs using small volumes of biofluids. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Serum tiRNAs are highly suited for development as biomarkers as they are stable, serum is easily accessible, and the custom Taqman assays described here are reliable and easy to perform. Further, we have recently developed an electrochemical direct detection method for quantification of tRNA fragments in small volume biofluids which could be utilized for prognostic profiling of patients upon entry into clinical trials ( McArdle et al , 2020 ). Therefore, we present a novel class of non-coding RNA, which may be of use as a prognostic biomarker indicating a protective neuronal stress response in ALS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Serum tiRNAs are highly suited for development as biomarkers as they are stable, serum is easily accessible, and the custom Taqman assays described here are reliable and easy to perform. Further, we have recently developed an electrochemical direct detection method for quantification of tRNA fragments in small volume biofluids which could be utilized for prognostic profiling of patients upon entry into clinical trials ( McArdle et al , 2020 ). Therefore, we present a novel class of non-coding RNA, which may be of use as a prognostic biomarker indicating a protective neuronal stress response in ALS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Participant history confirms these observations were not confounded by medications or observed in individuals with psychogenic non-epileptogenic seizures, further supporting tRFs as a potential predictor of epilepsy [57]. A follow-up study identified a third tRF, 5'GlyGCC, using electrochemical detection methods and qPCR on patient whole blood [58]. Compared to other RNA species, investigations into the role tRFs play in the diagnosis and prognosis of epilepsy are less abundant.…”
Section: Trnas and Epilepsymentioning
confidence: 64%
“…For stroke biomarkers to be of clinical use, rapid detection is crucial. A recent paper demonstrated that rapid detection of low concentrations of tRFs in plasma is indeed feasible [ 12 ]. We found that tRFs were also detectable in plasma depleted of extracellular vesicles, suggesting that circulating tRFs are mainly present outside vesicles.…”
Section: Discussionmentioning
confidence: 99%